1993
DOI: 10.1007/bf01720530
|View full text |Cite
|
Sign up to set email alerts
|

The effects of norepinephrine on hemodynamics and renal function in severe septic shock states

Abstract: Our results suggest that norepinephrine can be used safely in the treatment of severe septic shock states. Mean arterial pressure and glomerular filtration rate improved markedly without deleterious effects on CI, O2AVI and VO2I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2
7

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(69 citation statements)
references
References 23 publications
1
59
2
7
Order By: Relevance
“…The renal effects of NE are surprising because this drug usually improves diuresis without changing renal function in human septic shock and in other experimental designs (22). Despite an increase in perfusion pressure, NE did not change diuresis in the present model, suggesting that the effect on renal vascular resistances was more pronounced than on systemic resistances.…”
Section: Effects Of Drug Treatment On Diuresis and Renal Functioncontrasting
confidence: 53%
“…The renal effects of NE are surprising because this drug usually improves diuresis without changing renal function in human septic shock and in other experimental designs (22). Despite an increase in perfusion pressure, NE did not change diuresis in the present model, suggesting that the effect on renal vascular resistances was more pronounced than on systemic resistances.…”
Section: Effects Of Drug Treatment On Diuresis and Renal Functioncontrasting
confidence: 53%
“…The majority of the studies also find a significant increase in urinary output that may result from an increased GFR but also from pressure diuresis. An increase in GFR is only observed in three uncontrolled studies [56,62,64]. The only prospective randomized trial compares the effect of NE with high-dose dopamine.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…These interventions can be separated into measures designed to improve kidney perfusion and/or glomerular function or to modulate intrarenal pathophysiology. In sepsis-associated AKI, small and uncontrolled studies have shown that vasopressors can improve glomerular filtration (10,11). Renal-dose ("lowdose") dopamine, once widely used, is ineffective in improving kidney function in AKI, with the possible exception of increasing diuresis on the first day of use (12,13).…”
Section: Initial Consideration: Pharmacologic Interventions For Earlymentioning
confidence: 99%